Note on Online Auctions with Costly Bid Evaluation - Carr, Scott M. (Management Science, 2003)
As seen in the data of Snir and Hitt (2003), online service procurement auctions often end without achieving a contract despite active bidding, yet the existing auction literature is silent on why this occurs. One explanation for these unconsummated auctions may be that perfectly acceptable bids are submitted but disregarded because of the cost of assessing the bids' viability and the bidders' capabilities. This note examines this possibility by characterizing optimal and equilibrium bidding and bid-evaluation decisions in the presence of these costs.